The role of 18F-FDG PET or 18F-FDG-PET/CT in the evaluation of solitary pulmonary nodules. Issue 10 (October 2015) - Li, Wenbo; Pang, Hua; Liu, Qiong; Zhou, Jing
Highlights: Positron emission tomography (PET) or positron emission tomography/computed tomography (PET/CT) using 18 F-fluorodeoxyglucose ( 18 F-FDG) is a well-established functional imaging technique, makes a great contribution to the diagnosis and differential diagnosis of SPNs due to the high sensitivity of pathological accumulation of 18 F-FDG. Owing to integrates the anatomical morphological and metabolic aspects in a single examination, high sensitivity and the ability to perform whole-body scans, combined PET/CT improving overall diagnosis accuracy. Abstract: Even with the recent advance in diagnostic tools and techniques, solitary pulmonary nodules (SPNs) remains a major clinical challenge for all doctors involved in their study. There are a wide range of diagnoses of benign and malignant lesions that can manifest as SPNs. Positron emission tomography (PET) or positron emission tomography/computed tomography (PET/CT) makes a great contribution to the diagnosis and differential diagnosis of SPNs due to the high sensitivity of pathological accumulation of 18 F-FDG. Owing to integrates the anatomical morphological and metabolic aspects in a single examination, high sensitivity and the ability to perform whole-body scans, combined PET/CT improving overall diagnosis accuracy.